Misfolded polypeptides are selectively recognized and transported toward aggresomes by a CED complex - Joori Park (Nature Portfolio, 2017)
Misfolded polypeptide aggregates are actively transported to aggresomes, where they are degraded through aggrephagy. Here the authors show that these aggregates are selectively recognized by the CTIF–eEF1A1–DCTN1 (CED) complex and transported to aggresomes through the interactions of DCTN1 with dynein motors.